Penggunaan Algoritma A-Star Untuk Strategi Penyebaran Pengunjung pada Pusat Belanja - Lukman Hakim; Chyquitha Danuputri; Destriana Widvaninqrum (Universitas Budi Luhur, 2022)
Shopping centers such as malls that have many tenants or shops make it difficult for many people to find the intended store and the distribution of visitors is uneven, the existence of maps or instructions makes it easy to find the target shop, Bay walk mall which has ± 100 shops with buildings which is quite broad, it should be noted how the deployment and navigation of store search is easier. This study uses the A-Star algorithm to find the shortest route, based on the destination store. Navigation application testing was conducted on Baywalk Mall visitors with a success percentage of 86.6%